Determinants of Toddler’s Stunting in Coastal Area of Surabaya, East Java Indonesia - Mayasari, Ayu Citra; Rustam, Muh Zul Azhri; Priyantini, Dwi (International Conference on Sustainable Health Promotion, 2018)
Many factors influence stunting in the coastal area. This research aimed to analyze factors which have the influence of stunting toddler in the coastal area. This research used logistic regression analysis design with 145 pairs of child-mothers in coastal area Surabaya taken by stratified random sampling technique. Factors of economic status, level of education, genetic, and birth height is taken by questionnaire. Stunting measured by comparison of body weight and height of the toddler. The result shows that factor genetic of father and factor genetic of the mother has strong influence to stunting. Analyse was used ordinal regression with a sig. 0,007 (father's genetic) and sig 0,047 (mother's genetic). The Genetic of parents were very important to improve stunting of the toddler in a coastal area. What becomes the recommendation of this research was stunting can be saved with high selection couple if they want to get married.